Nonverbal Communication in artistic expression: El arte es una forma de encontrarnos a nosotros mismos - Gordo Alonso, María Concepción (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Nonverbal Communication is what we transmit without words. Also, everything that accompanies our words. It is inherent to the human being, it is part of our evolutionary history and is linked to the way we express emotions and feelings. In all facets and vital moments, we express ourselves through the body and we also receive information through it. If there is one area where it is especially important, it is art. The corporeality is a fundamental piece that helps the composition of the work and the expression of the message. In this work we will analyze three disciplines: Performance, Theater and Dance.